Improving Attention Network Function May Foster Medical Advances - Posner, Michael I.; Weible, Aldis P.; Voelker, Pascale; Rothbart, Mary K.; Niell, Cristopher M. (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Learning a skill involves an interaction between attention and memory [1]. Numerous studies have described how attention and memory interact when confronted with a choice point during skill learning. In both animal and human studies, pathways have been found that connect the executive and orienting networks of attention to the hippocampus [2]. The ability to modify these pathways provides the potential for improvement in addiction and other disorders. The anterior cingulate cortex, part of the executive attention network, is linked to the hippocampus via the nucleus reuniens of the thalamus. The parietal cortex, part of the orienting attention network, accesses the hippocampus via the entorhinal cortex. A recent model argues that mice employ two separate strategies during choice decisions [3]. Our study outlines two pathways by which attention and memory networks interact during skill learning [2]. These studies have led to specific predictions concerning the functional role of each pathway in connecting the cortex to the hippocampus. Here, we review some of the predictions arising from these studies were reviewed. Thereafter, the potential methods for manipulating the two pathways and assessing the directionality of their functional connections were discussed using viral expression techniques in mice. Finally, learning and stimulation of these pathways were discussed to know whether they can prove medically beneficial. We describe evidence for the treatment of addiction and depression. Treatment of demyelinating diseases such as chronic traumatic encephalopathy and multiple sclerosis are also discussed.